Mekanisme Pasar berdasarkan Pemikiran IBN Taimiyah - Zuhdi , Muhammad Naufal; Herman, Sebastian (FOCUS, 2024)
Islam is a perfect religion. Whether it's from a very small thing even to the affairs of state government. Everything is well calculated by Islam. It is inseparable in terms of the economy, in this case the market. Various economic thoughts emerged in the times. There are two contrasting economic systems. First, the capitalist economic system which promotes absolute freedom without any intervention from any party. Second, a socialist economic system that emphasizes the intense role of the government. The two systems each assume that they can improve the welfare of society. However, both failed to make it happen. Whether it's intervention from the government that is too deep, there are price games by buyers and sellers, to the market which is only controlled by a few business actors. Then the mechanism in Islam appears to be a solution. Therefore, this paper will discuss market mechanisms based on the opinion of Ibn Taimyah supported by the opinions of other scholars. It was found that the Islamic economic system takes a middle path. Which is not too liberating or vice versa, that is, to restrain.